Project-based learning integration with talking chips strategy for building self-confidence among vocational students - Muhammad Taufik Hilmawan; Muslikah, Muslikah; Rimayati, Elfi (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2025)
Purpose – This study aims to measure the effectiveness of implementing the Project-Based Learning (PjBL) talking chips method in classical guidance services to increase the self-confidence of students of class X TPFL 1 at SMK Negeri 7 Semarang. Method – This research used a quantitative approach and the PjBL method. The research subjects were 35 Class X TPFL 1 students, and the research was conducted at SMK Negeri 7 Semarang. The data analysis used a Paired T-Test. Result – The results showed that the data of the self-confidence scale results obtained an increase in the average value of the pretest of 50.23, postest 1 of 71.14, and postest 2 of 85.63, which shows that the project-based learning approach of talking chips technique in classical guidance is effective in increasing student confidence, especially with the application of interactive methods that encourage active involvement. Implication – The results of this study are expected to provide new variations for counseling teachers in conducting classical guidance learning with the talking chips technique, which can enhance student engagement in learning. Originality/Value – This research is the first to combine project-based learning and talking chip techniques in classical guidance services. *** Tujuan – Penelitian ini bertujuan untuk mengukur efektivitas penerapan metode Project-Based Learning (PjBL) talking chips dalam layanan bimbingan klasik untuk meningkatkan rasa percaya diri siswa kelas X TPFL 1 di SMK Negeri 7 Semarang. Metode – Penelitian ini menggunakan pendekatan kuantitatif dan metode PjBL. Subjek penelitian adalah 35 siswa kelas X TPFL 1, dan penelitian dilakukan di SMK Negeri 7 Semarang. Analisis data menggunakan Uji T Berpasangan. Hasil – Hasil penelitian menunjukkan bahwa data skala kepercayaan diri menunjukkan peningkatan nilai rata-rata pada pretest sebesar 50,23, postest 1 sebesar 71,14, dan postest 2 sebesar 85,63, yang menunjukkan bahwa pendekatan pembelajaran berbasis proyek dengan teknik talking chips dalam bimbingan klasik efektif dalam meningkatkan kepercayaan diri siswa, terutama dengan penerapan metode interaktif yang mendorong partisipasi aktif. Implikasi – Hasil penelitian ini diharapkan dapat memberikan variasi baru bagi guru bimbingan konseling dalam melaksanakan pembelajaran bimbingan klasik dengan teknik talking chips, yang dapat meningkatkan keterlibatan siswa dalam proses belajar. Orisinalitas/Nilai – Penelitian ini merupakan yang pertama kali menggabungkan pendekatan pembelajaran berbasis proyek dan teknik talking chips dalam layanan bimbingan klasik.